From Korea to Croatia: the first record of the polyclad flatworm Notocomplana koreana in the Mediterranean - KAPELLER, MAGDALENA A.; DITTMANN, ISABEL L.; EGGER, BERNHARD (Mediterranean Marine Science, 2024)
Polyclads are large-bodied, free-living flatworms that occur in diverse marine habitats. They are known predators of crustaceans, ascidians, snails, bivalves, polychaetes, and other flatworms. The acotylean genus Notocomplana Faubel, 1983 currently comprises 32 species that primarily inhabit the Pacific but are also found in the Atlantic and Indian Oceans. Here, we report the discovery of Notocomplana koreana (Kato, 1937) in the Mediterranean Sea. N. koreana was originally described from Korean and Japanese waters but was recently found to have expanded its range to the Atlantic. In this report, we shed light on the likely route of migration of N. koreana to the Mediterranean and discuss the challenges in identifying such an inconspicuous species. Through an integrative taxonomic approach, which merged morphological trait analysis using live animals and histology with a comparative genetic analysis of partial 28S ribosomal DNA and mitochondrial cytochrome c oxidase subunit I (COI) barcoding markers, we uncovered the characteristics of this introduced species and provide insights into its potential effect on Mediterranean ecosystems.